Dwaasheid of retoriek? Cornelis van Leeuwen en de ‘Belachelijke Geometristen’ - Nicolaije, Tim (Studium, 2012)
Foolishness or rhetoric? Cornelis van Leeuwen and the ’Ridiculous Geometrists’In 1663–1664 the inhabitants of Amsterdam were – probably much to their amusement – confronted with a pamphlet war between teachers of mathematics. This exchange of verbal and mathematical violence was instigated by Cornelis van Leeuwen, a young mathematics master (’rekenmeester’) who had just taken over the school of his former teacher at the Zeedijk. In his pamphlet he ridiculed some of his colleagues who, according to Van Leeuwen, were loudly proclaiming their mathematical skills while their publications merely showed trivialities or ideas they had stolen from others. The fact that Van Leeuwen resorted to such abusive language and mockery is generally seen as foolishness and an act of desperation on the part of someone who did not have the mathematical skills to keep up with his fellow ’rekenmeesters’. In this article, however, it is argued that when analysing the content of Van Leeuwen’s name-calling, a rhetorical strategy can be discovered that aimed at undermining the expertise and the honour of his opponents. Van Leeuwen argued that since they presented textbooks or exercises of others as their own, his opponents clearly did not comprehend the material themselves, thereby making them unsuitable to be teachers of mathematics. He furthermore claimed that by stealing from the works of other mathematicians, these ’ridiculous geometrists’ had acted dishonourably and should be seen as unreliable, an accusation with potentially serious consequences given the importance of honour and reliability in early-modern Dutch society. Even though Van Leeuwen’s attempt to discredit and dishonour some of his competitors on the Amsterdam mathematical market completely backfired, it is nevertheless instructive to see the rhetorical strategy of his pamphlet, which shows us how interwoven mathematical practices were with the general culture of that time.